Decentralized Identity in FinTech: Blockchain Based Solutions for Fraud Prevention and Regulatory Compliance - Yuni T, Veronika; Soderi, Ahmad (Indonesian Scientific Publication, 2025)
The FinTech sector is facing escalating threats from identity theft and digital fraud, with global losses exceeding US42 billion annually. This study explores how blockchain based identity systems particularly Verifiable Credentials (VC), Decentralized Identifiers (DID), and selective disclosure protocols can enhance digital security, reduce onboarding time, and ensure compliance with evolving global standards. A qualitative and comparative methodology was applied, analyzing data from regulatory bodies (FTC, FATF, NIST), industry case studies, and technical frameworks (OpenID4VC, SD JWT, W3C). Results reveal that blockchain identity solutions reduce fraud risk by preventing synthetic identity use, while significantly improving authentication success rates through biometric and passkey based logins. Reusable KYC models integrated with VC/DID frameworks cut onboarding durations from weeks to days, demonstrating substantial operational efficiency. Furthermore, alignment with GDPR, eIDAS 2.0, and AML/CFT standards confirms the regulatory readiness of these systems. The findings suggest that decentralized identity offers a viable, scalable alternative to traditional identity verification, enabling secure, privacy preserving, and user controlled authentication. Despite challenges such as integration complexity and regulatory fragmentation, the strategic advantages in security and compliance position blockchain identity systems as essential tools for the future of FinTech.